Differential effects of insecticides on mitochondrial membrane fluidity and ATPase activity between the wolf spider and the rice stem borer - Hai-ping LI; Jing CHANG; Tao FENG; Xi-wu GAO (Journal of Integrative Agriculture, 2015)
Differential effects of methamidophos and three pyrethroids on ATPase activity and membrane fluidity of mitochondria were investigated between the wolf spider (Pirata subpiraticus (Boes. et Str.)) and the rice stem borer (Chilo suppressalis (Walker)). Based on a comparison of LD50 values, the toxicities of the tested insecticides were higher to the wolf spider than to the rice stem borer. Cyhalothrin at 1×10−4 mmol L−1 caused inhibition of the mitochondrial Na+-K+-ATPase and Ca2+-Mg2+-ATPase activities, and it's inhibitions on Na+-K+-ATPase and Ca2+-Mg2+-ATPase activities were significantly higher in the wolf spider (44 and 28%) than in the rice stem borer (19 and 11%). Methamidophos at 1×10−4 mmol L−1 decreased Ca2+-Mg2+-ATPase activity by 16 and 27% in the wolf spider and the rice stem borer, respectively, but no significant effect on the specific activity of Na+-K+-ATPase was observed. The DPH (1,6-diphenyl-1,3,5-hexatriene) fluorescence polarization values of mitochondrial membranes were not significantly affected by methamidophos in either species. However, cyhalothrin and alpha-cypermethrin induced the values of DPH polarization of mitochondrial membrane increasing with the concentration of cyhalothrin and alpha-cypermethrin from 20 to 100 μmol L−1 in the rice stem borer and the wolf spider. Effect of ethofenprox on fluidity of the wolf spider and the rice stem borer was contrary. These results suggest that both inhibition of membrane ATPase and changes of membrane fluidity could be appended to the action mechanisms of pyrethroid insecticides.